THE ROLE OF MUNAVVAR KORI ABDURASHIDKHANOV IN THE EMERGENCE OF THE NATIONAL JADID MOVEMENT - Mukhammadiev Lochin Gayratovich (Web of Journals Publishing, 2025)
The article examines the Jadid movement in the country and the history of its emergence. The book also briefly discusses the unrivaled contribution of Munavvarkori Abdurashidkhanov, one of the great enlightened Jadids, to the Jadid movement and his life.
Keywords: National Jadidism, Munavvar kori Abdurashidkhanov, Usuli Jadid, Usuli Savtiya, old school, new school, Turkish literacy and Turkestan national publications